REPRESENTASI IDOLA BARU KOREA: STUDI KASUS PROGRAM ACARA RAGAM KOREA SELATAN STREET WOMAN FIGHTER - Hasanah, Ummul; Handayani, Andri; Kusumaning Ratri, Ajeng (Jurnal Muara Ilmu Sosial, Humaniora, dan Seni, 2025)
This study aims to examine the representation of new South Korean female idols as reflected in the dance crew on Street Woman Fighter and how the discourse on street woman dancers is depicted through this broadcast in accordance with Stuart Hall's representation theory. The theory of representation used is specifically a constructionist approach through the production of meaning and the production of discourse. The research method used is a qualitative method with a literature study data collection technique with the main text of the SWF program broadcast on Mnet which is accessed via VIU's paid over-the-top video service in December 2021. In addition, the author also examines various sources of literature as secondary data sources. such as books, journal articles, articles from websites and social media as a complement to data analysis. The results of the study show that the representation of new Korean idols represented by dance crews participating in Street Woman Fighter is very close to the images of street dancers and hip hoppers which are dominated by men. The image of street culture and hip hopper can be seen from the style of dress, style of makeup, tattoos on the body, style of speech and dance battle shown. Even though it brings fresh air to the world of television content by appointing background dancers as the main characters, Street Woman Fighter is not free from representational problems. Some of the problems that arise are the incompatibility between the promotional material and the title of the program being broadcast, there is a process of changing the image of female idols who are feminine, refined and beautiful, there is a process of masculinizing the image of female dancers participating in SWF events, and the role of the media in building the image of a street dancer or This street fighter is especially in the content editing process. Keywords: representation; self-image; street dance; hip hop; Street Woman Fighter